Three Dimensional Integrated Circuit Design EDA, Design and Microarchitectures - Xie, Yuan.; Cong, Jason; Sapatnekar, Sachin; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
This book presents an overview of the field of 3D IC design, with an emphasis on electronic design automation (EDA) tools and algorithms that can enable the adoption of 3D ICs, and the architectural implementation and potential for future 3D system design. The aim of this book is to provide the reader with a complete understanding of: the promise of 3D ICs in building novel systems that enable the chip industry to continue along the path of performance scaling, the state of the art in fabrication technologies for 3D integration, the most prominent 3D-specific EDA challenges, along with solutions and best practices, the architectural benefits of using 3D technology, architectural-and system-level design issues, and the cost implications of 3D IC design. Three Dimensional Integrated Circuit Design: EDA, Design and Microarchitectures is intended for practitioners in the field, researchers and graduate students seeking to know more about 3D IC design.
3D Process Technology Considerations -- Thermal and Power Delivery Challenges in 3D ICs -- Thermal-Aware 3D Floorplan -- Thermal-Aware 3D Placement -- Thermal Via Insertion and Thermally Aware Routing in 3D ICs -- Three-Dimensional Microprocessor Design -- Three-Dimensional Network-on-Chip Architecture -- PicoServer: Using 3D Stacking Technology to Build Energy Efficient Servers -- System-Level 3D IC Cost Analysis and Design Exploration.
Keywords: Engineering; Electronics; Optical materials; Surfaces (Physics).; Engineering; Electronics and Microelectronics, Instrumentation; Optical and Electronic Materials; Surfaces and Interfaces, Thin Films; Engineering, general